(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: To investigate and compare the resistance of roots to vertical fracture after the retrieval of a separated instrument from the root canal, followed by endodontic treatment using different root canal sealers. Methodology: Ninety extracted mandibular single-rooted premolars were collected and decoronated at CEJ. Roots were then randomly divided into six groups of 15 each: two control groups – Group A (negative control) and Group B (positive control) – and four experimental groups – Groups C, D, E, and F. In four of the experimental groups and one control group (Group B), the rotary instrument (orifice shaper) fractured in the middle third of the root canal. The fractured file was then removed with a Masserann kit. Following instrument retrieval, the canals were prepared with ProTaper up to F2, and obturation was done with gutta-percha (GP) points and four different sealers using lateral compaction, as follows: GROUP A (negative control): obturation was carried out with GP points and Tubliseal sealer; GROUP B (positive control): the instrument was retrieved and no obturation was done; GROUP C: obturation was carried out with GP points and Tubliseal; GROUP D: obturation was carried out with GP points and MTA; GROUP E: obturation was carried out with GP points and AH Plus sealer; and GROUP F: obturation was carried out with GP points and Resilon sealer. The coronal seal was done using GIC. Each specimen was tested for fracture resistance using the Instron universal testing machine. Results: All the experimental groups, as well as the negative control group (Group A), showed higher ultimate strength compared to Group B. All the experimental groups, as well as Group B, had significantly lower ultimate strength compared to Group A. Among the experimental groups, the only significant difference observed was between Group D (Resilon) and Group F (MTA) (p = 0.041). Group F had significantly higher ultimate strength compared to Group D. None of the other differences were significant statistically. Conclusion: All the fractured instruments were successfully removed from the middle third of the root canal with considerable loss of dentin. Resilon and MTA provided a replacement for root dentin when used as obturating materials. Clinical significance: The prevalence of broken instruments ranges from 0.5% to 5%. If the broken file prevents adequate cleaning of the canal beyond the obstruction, the treatment outcome is adversely affected. Frequently, this leads to the failure of root canal therapy and increases patient anxiety. The definitive treatment in the management of root canal instrument fracture is therefore removal.